Impact of Working Capital Management on Profitability of Small-Scale Enterprises: The Case of Wolaita Sodo Town, Southern Ethiopia - Eyasu, Admasu; Rao, Durga; Belachew, Tedeme; Khater, Maya; Mohamed Rafi, Sharmili; Senapathy, Marisennayya (Shanlax International Journal of Management, 2025)
Working capital management has become an important topic for the profitability of small-scale enterprises. There for this research objective is formulated in the study to investigate the impact of working capital management on the profitability of small-scale enterprises and provide recommendations for the rate of return in Sodo town. In this light, the study in its first section gives a background to the study and the second part is a detailed literature review on working capital management, third tools and assessment models, Quantitative research design is employed, and under the quantitative research design survey method is used. The data will be collected by cross-sectional survey method. The fourth part of this study is an analysis of primary data by descriptive statistical tools and hypothesis testing using a regression model. This leads the researcher to conclude in the last section that SSEs with good working capital management practices have lower problems of earning rates and relatively higher profitability of enterprises.